Natural Training in Control of Formal Education: A Critical Analysis ofthe Book " Zaynab Letters" - seyyed hosyn hoseyni (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The difference between formal education and education training, based on the human and divine nature of the individual mechanisms, has always been one of the most important issues in the field of philosophy of education and has been considered the analysis of educational characteristics education.The main objective of this paper is to analyze the book "Zaynab Letters" through which the dimensions of these differences are explored; a general conceptual framework regarding prominent challenges in the formal education system and conceptual hurdles posed by the events in this book are discussed. .The paper aims to find out what  the principles and characteristics of children's innate language are. The author has attempted to find out the analytical methods, achieve these aspects in the dual interpretation of its provisions. Finally, after analyzing the content of the book, as the conclusion of the paper, the nine principles regarding the language characteristics of children are identified, and then the twelve special features and components of the language are considered. Furthermore,  some solutions from previous findings to change the formal education referring  to indigenous education are provided.